Ответы и объяснения

Лучший Ответ!
2013-09-09T16:39:03+04:00
2sinx -√3 tgx - 2√3 cosx+3=02sinxcosx-sqrt(3)sinx-2sqrt(3)*cos^2x+3cosx=0sinx(2cosx-sqrt(3))-cosx*sqrt(3)(2cosx-sqrt(3))=0(2cosx-sqrt(3))(sinx-cosx*sqrt(3))=0cosx=sqrt(3)/2           sinx-sqrt(3)cosx=0  tgx=sqrt(3)x=+-П/6+2Пk                                              x=П/3+Пk
2013-09-09T16:40:53+04:00
Решение: 
2sinx-√3tgx-2√3cosx+3=0 
(2sinx-2√3cosx)-(√3tgx-3)=0 
2cosx(tgx-√3)-√3(tgx-√3)=0 
(tgx-√3)(2cosx-√3)=0 
a) tgx-√3=0 
tgx=√3 
x1=π3+πn 
б) 2cosx-√3=0 
сosx=√3/2 
x2=±π/6+2πn